Recent challenges for the enforcement of wildlife laws in East Malaysia - Ho Nyuk Onn @ Ariffin, Mariani (Universiti Putra Malaysia Press, 2018)
Law enforcement is one of the weakest links in wildlife conservation. This paper analyses the main challenges facing wildlife law enforcement in East Malaysia and identifies the enforcement strategy used by wildlife officers in the region. To these ends, a questionnaire was distributed to the wildlife officers. The study found that the respondents tended towards deterrence strategy in enforcing the laws which focuses on detecting and punishing violations. The study also revealed that the primary challenge facing the wildlife enforcement officers was lack of institutional capacity. This was reflected by problems related to inadequate equipment, facilities, limited manpower and lack of skills. Other major challenges highlighted by the respondents were lack of cooperation from the public and other enforcement agencies, lack of political will and threats from the regulated parties. The findings of the study contribute to a greater understanding of the main enforcement strategy used by wildlife officers in East Malaysia and highlight challenges they encountered in undertaking their duties. These insights provide useful information into developing better informed capacity-building programme for the wildlife officers and for decision-makers at state and federal level in determining allocation or other provision for the wildlife authorities.